Public Policies around the Exploitation of Yasuní ITT: Desires or Basic Needs? - Manobanda Núñez, Bolívar Lenin (2025)
The main objective is to analyse public policies surrounding the Yasuní ITT project in Ecuador, evaluating whether they respond to economic desires or basic needs, especially of Amazonian indigenous communities. The methodology includes a critical review of literature, analysis of government decrees, and specific case studies, such as the impact on the Waorani indigenous community. The research distinguishes between desires and needs, using Wiggins’ approaches, which differentiate needs by their independence from the individual’s mental state and their grounding in reality and human wellbeing, and desires as intentional and arbitrary. Carlos S. Nino and Harry Frankfurt reinforce the primacy of basic needs such as food, shelter, and security over desires. Yasuní ITT is an example of how public policies in Ecuador have favored the economic interests of the oil industry, through decrees allowing exploitation in protected areas, leading to deforestation and impacts on biodiversity and the health of indigenous communities. The research concludes that these policies prioritize desires of elites and transnationals over the basic needs of local indigenous communities like the Waorani indigenous people, perpetuating unsustainable and unequal development.